"Foreign Locals": Transnationalism, Expatriates, and Surfer Identity in Costa Rica. (June 2017) - Usher, Lindsay E.
Surfer identity construction has been linked to a number of factors, including a strong attachment to place. Surfers have always been a mobile population, and the search for waves in new places is a central aspect of the sport. The movement of surfers has led to the development of transnational communities in surf destinations. This ethnographic study examined the ways in which expatriates in Costa Rica construct their identities as local surfers. Many expatriates considered themselves local surfers as a result of the time they had lived and surfed in Pavones and their knowledge of the wave. Many Ticos did not think of expatriates as local surfers. Some expatriates' assertions of local identity and resultant aggression were sources of frustration for Ticos, tourists, and other expatriates.